Toward a green revolution in Africa: What would it achieve, and what would it require? - Diao, Xinshen; Headey, Derek D.; Johnson, Michael E. (Wiley, 2008)
The current global food crisis has reemphasized the costliness of Africa's failure to achieve food security and poverty reduction. The instrument by which other more successful developing countries achieved these outcomes was a “Green Revolution” in agriculture. While previous research has provided largely discursive appraisals of the viability of an African Green Revolution, this article adopts a more rigorous methodology to address that question. First, an economy‐wide multimarket model, augmented with existing poverty–growth elasticities, is developed to assess the likely impacts of a rapid acceleration in food production (of the kind witnessed in previous Green Revolutions) on food prices, consumption and demand, farmer revenue, and poverty. Our results suggest that a rapid growth in staple production, together with more integrated regional markets, would reduce food prices by roughly 20–40% for consumers and 10–20% for producers among the major crops. This translates into a large rise in farm revenues, annual agricultural growth rates of 6.5% or higher, broader income growth and food security, and over 70 million Africans being lifted out of poverty. The article concludes by emphasizing the kinds of fundamental policy actions and resources that would be required for achieving these outcomes.